The Nereid on the rise: Platynereis as a model system - Özpolat, B. Duygu; Randel, Nadine; Williams, Elizabeth A.; Bezares Calderón, Luis Alberto; Andreatta, Gabriele; Balavoine, Guillaume; Bertucci, Paola; Ferrier, David E. K.; Gambi, Maria Cristina; Gazave, Eve; Handberg-Thorsager, Mette; Hardege, Jörg; et al. (EvoDevo, 2021)
The Nereid Platynereis dumerilii (Audouin and Milne Edwards (Annales des Sciences Naturelles 1:195-269, 1833) is a marine annelid that belongs to the Nereididae, a family of errant polychaete worms. The Nereid shows a pelago-benthic life cycle: as a general characteristic for the superphylum of Lophotrochozoa/Spiralia, it has spirally cleaving embryos developing into swimming trochophore larvae. The larvae then metamorphose into benthic worms living in self-spun tubes on macroalgae. Platynereis is used as a model for genetics, regeneration, reproduction biology, development, evolution, chronobiology, neurobiology, ecology, ecotoxicology, and most recently also for connectomics and single-cell genomics. Research on the Nereid started with studies on eye development and spiralian embryogenesis in the nineteenth and early twentieth centuries. Transitioning into the molecular era, Platynereis research focused on posterior growth and regeneration, neuroendocrinology, circadian and lunar cycles, fertilization, and oocyte maturation. Other work covered segmentation, photoreceptors and other sensory cells, nephridia, and population dynamics. Most recently, the unique advantages of the Nereid young worm for whole-body volume electron microscopy and single-cell sequencing became apparent, enabling the tracing of all neurons in its rope-ladder-like central nervous system, and the construction of multimodal cellular atlases. Here, we provide an overview of current topics and methodologies for P. dumerilii, with the aim of stimulating further interest into our unique model and expanding the active and vibrant Platynereis community.